The origin of S0s in clusters: evidence from the bulge and disc star formation histories - Johnston, Evelyn J.; Aragón-Salamanca, Alfonso; Merrifield, Michael R. (Oxford University Press, 2014)
The individual star formation histories of bulges and discs of lenticular (S0) galaxies can provide information on the processes involved in the quenching of their star formation and subsequent transformation from spirals. In order to study this transformation in dense environments, we have decomposed long-slit spectroscopic observations of a sample of 21 S0s from the Virgo Cluster to produce one-dimensional spectra representing purely the bulge and disc light for each galaxy. Analysis of the Lick indices within these spectra reveals that the bulges contain consistently younger and more metal-rich stellar populations than their surrounding discs, implying that the final episode of star formation within S0s occurs in their central regions. Analysis of the α-element abundances in these components further presents a picture in which the final episode of star formation in the bulge is fuelled using gas that has previously been chemically enriched in the disc, indicating the sequence of events in the transformation of these galaxies. Systems in which star formation in the disc was spread over a longer period contain bulges in which the final episode of star formation occurred more recently, as one might expect for an approximately coeval population in which the transformation from spiral to S0 occurred at different times. With data of this quality and the new analysis method deployed here, we can begin to describe this process in a quantitative manner for the first time.